Broaching goals‐of‐care conversations in advancing pediatric cancer. Issue 10 (6th August 2021) - Kaye, Erica C.; Woods, Cameka; Velrajan, Srilakshmi; Lemmon, Monica E.; Baker, Justin N.; Mack, Jennifer W.
Abstract: Broaching conversations about goals of care can be difficult for clinicians. Presently, the communication strategies used by pediatric oncologists to approach goals of care conversations are not well understood. We recorded disease re‐evaluation conversations between pediatric oncologists, patients, and parents, capturing 141 conversations (∼2400 minutes) for 17 patients with advancing illness across the study period. We conducted content analysis to identify strategies for broaching goals‐of‐care conversations and found five distinct communication approaches, which were not mutually exclusive. Further research is needed to explore patient and family views on best practices for broaching discussions about goals of care.